Peran Pola Asuh Orang Tua dalam Mengembangkan Kemampuan Empati Anak Usia Dini - Aira Ridzqikha Amalia Salsabila Putri Arisman; Randiawan Randiawan (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2026)
This study aimed to describe the development of empathy in early childhood based on parenting styles. The study employed a quantitative approach with a correlational design. The participants consisted of 77 children Group B Sigi Regency. Data on parenting styles were collected through questionnaires, while children's empathy was assessed through observation. The results showed that democratic parenting was the most frequently applied parenting style (50.64%), followed by authoritarian parenting (25.97%) and permissive parenting (23.37%). Children raised under authoritarian parenting were predominantly categorized as being in the emerging stage of empathy development (50%). In contrast, most children raised under democratic parenting were categorized as developing as expected (53.84%), and no children were found in the underdeveloped category. Similarly, children raised under permissive parenting were mostly categorized as developing as expected (55.55%), although some were still classified as underdeveloped. The findings indicate that empathy development tends to be better among children who experience democratic parenting compared to those raised under authoritarian and permissive parenting styles. This study contributes to the growing body of knowledge on empathy as an essential aspect of young children's socio-emotional development and provides valuable insights for parents and educators in implementing parenting practices that support the development of empathy in early childhood.